Effect of beta-adrenergic stimulation on whole-body and abdominal subcutaneous adipose tissue lipolysis in lean and obese men. - Jocken, J; Goossens, G; van Hees, A; Frayn, K; van Baak, M; Stegen, J; Pakbiers, M; Saris, W; Blaak, E (Springer-Verlag, 2008)
AIMS/HYPOTHESIS: Obesity is characterised by increased triacylglycerol storage in adipose tissue. There is in vitro evidence for a blunted beta-adrenergically mediated lipolytic response in abdominal subcutaneous adipose tissue (SAT) of obese individuals and evidence for this at the whole-body level in vivo. We hypothesised that the beta-adrenergically mediated effect on lipolysis in abdominal SAT is also impaired in vivo in obese humans. METHODS: We investigated whole-body and abdominal SAT glycerol metabolism in vivo during 3 h and 6 h [2H5]glycerol infusions. Arterio-venous concentration differences were measured in 13 lean and ten obese men after an overnight fast and during intravenous infusion of the non-selective beta-adrenergic agonist isoprenaline [20 ng (kg fat free mass)(-1) min(-1)]. RESULTS: Lean and obese participants showed comparable fasting glycerol uptake by SAT (9.7+/-3.4 vs 9.3+/-2.5% of total release, p=0.92). Furthermore, obese participants showed an increased whole-body beta-adrenergically mediated lipolytic response versus lean participants. However, their fasting lipolysis was blunted [glycerol rate of appearance: 7.3+/-0.6 vs 13.1+/-0.9 micromol (kg fat mass)(-1) min(-1), p<0.01], as was the beta-adrenergically mediated lipolytic response per unit SAT [Delta total glycerol release: 140+/-71 vs 394+/-112 nmol (100 g tissue)(-1) min(-1), p<0.05] compared with lean participants. Net triacylglycerol flux tended to increase in obese compared with lean participants during beta-adrenergic stimulation [Delta net triacylglycerol flux: 75+/-32 vs 16+/-11 nmol (100 g tissue)(-1) min(-1), p=0.06]. CONCLUSIONS/INTERPRETATION: We demonstrated in vivo that beta-adrenergically mediated lipolytic response is impaired systematically and in abdominal SAT of obese versus lean men. This may be important in the development or maintenance of increased triacylglycerol stores and obesity.